An evaluation of inertial motion capture technology for use in the analysis and optimization of road cycling kinematics - Cockcroft, Stephen John (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2011.